Is morphine still the best reference opioid?. (January 2012) - Gálvez, Rafael; Pérez, Concepción
SUMMARY  Cancer and noncancer pain can usually be managed according to the WHO analgesic ladder and, in many countries, morphine remains the first-line opioid of choice for chronic severe pain. There have been many advances in the use of opioids for moderate-to-severe pain control in recent years. Consequently, the position of morphine as the gold standard became gradually more questioned, mostly because of serious adverse effects and the availability of different opioids and new formulations. The place of morphine as the first-line option is based on reasons of familiarity, availability or cost rather than medical advantages. In recent years, a number of systematic reviews failed to demonstrate superiority of morphine over other opioids in terms of efficacy or tolerability. Moreover, some strong opioids have shown improved tolerability or convenience. Currently, morphine might still be considered as a reference drug for equivalent dosing, but not for strategic healthcare decisions, as it has not demonstrated clinical or pharmacological superiority over other opioids. Therefore, there is a lack of evidence to sustain the role of morphine as the gold standard in the treatment of chronic severe pain.